(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Values of exclusive leadership characterize the administration of the neoliberal university, but are incongruous with values of inclusive leadership often enacted in the work of teaching, learning, and research. This article explores how an action research project to advance inclusive leadership at Royal Roads University adapted a visual data elicitation method and used metaphor analysis to reveal opportunities to align espoused, communicated, and enacted values. Images evoke metaphors (Mumby & Spitzack, 1983; Vakkayil, 2008) that enable researchers engaged in their own organizational development to elicit creative possibilities that are “covered up by the familiarity of everyday experience” (Koch & Deetz, 1981, p. 13). By eliciting desired qualities associated with inclusive leadership (Rayner, 2009), we have been able to make visible and model inclusive messages, structures, behaviours, strategies, and actions as the building blocks of a culture built on the value of inclusivity and collaboration, and the principles of diversity and interdependence. One key insight of the research is that arts-based action research effectively equips academic and administrative leaders to transcend deficit-based problem solving and the reductionism associated with neoliberal university management and to approach organizational development with the creative energy that arts-based research inspires.